2008
DOI: 10.1016/j.neuropharm.2007.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin inhibits endocannabinoid-sensitive hippocampal IPSPs and stimulates others

Abstract: Cholecystokinin (CCK) is the most abundant neuropeptide in the central nervous system. In the hippocampal CA1 region, CCK is co-localized with GABA in a subset of interneurons that synapse on pyramidal cell somata and apical dendrites. CCK-containing interneurons also uniquely express a high level of the cannabinoid receptor, CB 1 , and mediate the retrograde signaling process called DSI. Reported effects of CCK on inhibitory post-synaptic potentials (IPSPs) in hippocampus are inconsistent, and include both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 62 publications
5
48
0
Order By: Relevance
“…This study revealed that CCK acts on the two types of inhibitory inputs in the opposite ways, namely, activation of one type and inhibition of the other. In agreement with this notion, it was reported that CCK selectively suppresses carbachol-induced spontaneous IPSPs, which reflect the inputs from CB 1 -and CCK-positive basket cells (259). The CB 1 dependency of this effect remains to be determined.…”
Section: Hippocampussupporting
confidence: 56%
“…This study revealed that CCK acts on the two types of inhibitory inputs in the opposite ways, namely, activation of one type and inhibition of the other. In agreement with this notion, it was reported that CCK selectively suppresses carbachol-induced spontaneous IPSPs, which reflect the inputs from CB 1 -and CCK-positive basket cells (259). The CB 1 dependency of this effect remains to be determined.…”
Section: Hippocampussupporting
confidence: 56%
“…According to the 'Cnr1 receptor hypothesis', CCK activation of CCKBR initiates endocannabinoid synthesis, activating pre-synaptic Cnr1 on CCK-containing interneurons to inhibit GABA transmission. Separately, CCK strongly depolarizes parvalbumin interneurons via CCKBR, increasing firing frequency of inhibitory currents (Foldy et al, 2007;Karson et al, 2008;. Although our results suggest that CCKBR is downstream of Cnr1, cell-type specific behavioral studies will better clarify the differences in our respective models of a Cnr1-CCKBR interaction.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, agatoxin enhances the relative magnitude, although not the absolute magnitude, of DSI by blocking interneurons that are not susceptible to DSI (Lenz et al 1998). Alternatively, the greater suppression of GABA A eIPSPs in agatoxin could reflect the removal of a presynaptic interaction between different kinds of s. radiatum interneurons, as recently suggested (Karson et al 2008).…”
Section: Iltd In Conotoxin and Enhancement Of Mglur-initiated Eipsp Smentioning
confidence: 80%
“…It is not fully understood how different interneurons are regulated, or how they interact with each other, although various hypotheses are emerging (e.g., Buzsaki 2002;Gillies et al 2002;Hefft and Jonas 2005;Glickfeld and Scanziani 2006;Karson et al 2008). Hoffman and Lupica (2000) showed that the GABA A (but not the GABA B ) component of an evoked inhibitory postsynaptic current was sensitive to an exogenous cannabinoid agonist, while both components were sensitive to the selective µOR agonist, [D-Ala2, NMePhe4, Gly-ol5]-enkephalin (DAMGO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation